(untitled) (Global Journal of Science Frontier Research, 2014)
On-farm intervention strategies based on feeding and general management practice including hygiene and sanitation towards on the reduction of occurrence of external and gastrointestinal parasites and sub clinical mastitis on cross breed lactating dairy cows was conducted during the dry season in West Shewa Zone, central Ethiopia. A total of 34 cows in early to mid lactation with an average body weight of 369.29 ±38.58 kg were selected based on parity, milk yield, days in milk, body weight and health status and assigned in to two groups; 17 cows of one group were maintained as farmers’ usual practice (control diet = T 0 ), and the rest 17 were supplemented with urea-molasses multi-nutrient block (UMMB) together with a concentrate mixture (55% wheat bran, 43 % linseed cake and 2% salt) in natural pasture hay based diet under stall feeding condition (intervention diet = T 1 ). Moreover, the udder and associated hygienic condition of cows in T 1 group were implemented by farmers as per the advice and follow up of the researchers and veterinarians. The study showed that, the prevalence of gastrointestinal parasites (41.2%), external parasites (ticks) (47.1%) and sub clinical mastitis (47.1%) in the T 0 group was significantly (P